Identification of exotic pest and Australian native and naturalised species of Tetranychus (Acari: Tetranychidae) - Seeman, Owen D.; Beard, Jennifer J. (Zootaxa, 2011)
An illustrated dichotomous key to the 3 endemic Australian, 9 naturalised exotic, and 14 exotic pest species of Tetranychus Dufour, 1832, deemed to be of greatest risk of accidental introduction to Australia is presented. Each species is diagnosed, illustrated with line drawings and/or photographs, and supplied with remarks on its biology, potential to enter Australia and economic importance. We establish that Tetranychus desertorum Banks, 1900, previously thought to be present in Australia, is absent. The erroneous record of T. desertorum is due to confusion between this species and T. ludeni. Tetranychus gloveri Banks, 1900 was absent from Australia until a recent incursion in Darwin, now considered eradicated. All previous records of Tetranychus gloveri, Tetranychus tumidus Banks, 1900 and Allonychus braziliensis (McGregor, 1950) in Australia are Oligonychus digitatus Davis, 1966. Tetranychus ludensis Attiah, 1969 syn. nov. is synonymised with Tetranychus ludeni Zacher, 1913. Lectotype and paralectotype specimens are designated for Tetranychus marianae McGregor, 1950 and Tetranychus mexicanus (McGregor, 1950).